Goods and services tax registrant's satisfaction on taxpayer access point system and its determinants - Lee, Chai Peng (2018)
Taxpayer Access Point (TAP) System being introduced to Malaysian by Royal Malaysian Customs Department (RMCD) on 1 June 2014 in conjunction with the implementation of the Goods and Services Tax (GST). Based on the data provided by RMCD, 98% of the total GST registrants used TAP System to submit their electronic return timely. Due to the overwhelming acceptance of the system after the system being launched, it is important to know the determinants which influence this high usage of the system and to know their satisfaction level. Therefore, this study proposes two main objectives which are to determine the determinants which influence GST registrants’ intention to use TAP System and to examine how GST registrants’ intention to use TAP System can influence their satisfaction towards TAP System. This study used variables namely attitude, subjective norms, and perceived behavioural control from Theory Planned Behaviour. This study also integrates variables perceived ease of use and perceived usefulness from Technology Acceptance Model to investigate the determinants that influence GST registrants’ intention to use TAP System. A total of 180 useable surveys were received from GST Processing Centre and RMCD GST offices which located at Kuala Lumpur and Putrajaya. Total of six hypotheses are tested in this study. All the hypotheses are tested using multiple regression analysis. Results showed that 69.5% of the variance in intention to use TAP system is explained by variables attitude, perceived ease of use and perceived usefulness. Variables perceived behavioural control and subjective norms do not showed significant related in this study. Meanwhile, 60.9% of the variance user satisfaction towards TAP system is explained by intention to use TAP System. Implication on the theory and the policy maker are also discussed in this study.